Pathophysiological basis of translational stroke research - Hossmann, Konstantin-Alexander (Folia Neuropathologica, 2009)
The high incidence and the devastating consequences of stroke call for efficient therapies but despite extensive experimental evidence of neuroprotective improvements, most clinical treatments have failed. The poor translational success is attributed to the inappropriate selection of clinically irrelevant animal models, the inappropriate focus on clinically irrelevant injury pathways and the inappropriate estimation of the length of therapeutic windows. To substantiate this conclusion, the pathophysiology of experimental stroke is reviewed. Particular emphasis is placed on the importance of collateral pathways, the penumbra concept and the viability thresholds of ischaemia, the haemodynamic and molecular mechanisms of injury evolution and the effect of secondary complications, notably inflammation and brain oedema. The comparison of permanent and transient focal ischaemia, on the one hand, and between mechanical and thrombolytic reperfusion, on the other, reveal basic differences in the mechanisms and dynamics of injury evolution which are of paramount importance for the proper targeting and time window of therapeutic interventions. These differences must be considered for adequate modelling of preclinical stroke studies to avoid unsuccessful translation of experimental data to the clinical setting.